Climate vulnerability assessment of the Espeletia Complex on Páramo Sky Islands in the Northern Andes - Valencia Garcia; Jhon Brayan (2021)
Evaluation of the climate-anthropic effects on paramos ecosystem in northern andes region (Colombia). (2021-08)